Grossing Breast Cancer Specimens: A Comprehensive Review. Issue 4 (July 2020) - Agarwal, Apeksha N.; Ritter, Jacob; Dornbluth, Nella C.; Mais, Daniel D.; Nazarullah, Alia N.
Abstract : Abstract: Grossing breast specimens presents a unique challenge in the anatomic pathology laboratory, because the approach varies with the type of specimen received, the preoperative diagnosis, and the administration of neoadjuvant therapy. Furthermore, careful attention to preanalytic variables, such as time of fixation, is required. The specimen often lacks orienting anatomic landmarks, and accurately documenting margins in 3 dimensions requires a deliberate approach that is easily understood for future reference. This article will provide a comprehensive source for grossing commonly received breast specimens, ranging from surgical biopsies to modified radical mastectomies and will describe the proper care of preanalytical measures to avoid compromise of biomarkers, methods to ensure adequate sampling of tissue for diagnosis, and assessment of tumor burden following neoadjuvant treatment.